Firm Productivity, innovation and Financial Development - Verdier, Genevieve (IMF Working Papers; Working Paper ;, 2010)
How do firm-specific actions-in particular, innovation-affect firm productivity? And what is the role of the financial sector in facilitating higher productivity? Using a rich firm-level dataset, we find that innovation is crucial for firm performance as it directly and measurably increases productivity. Moreover, its effects on productivity are mediated through the financial sector; firms reap the maximum benefits from innovation in countries with well-developed financial sectors. This effect is particularly important for firms in high-tech sectors, which typically have higher external financing needs.